Cartão de residente municipal: instrumento para aprimoramento da gestão no município: o caso de Louveira, SP - Rodrigues, Messias Marques (2015)
To implement public policies in the municipalities, one of the problems is the absence of data to inform the reality of the local situation, which shows the benefit and necessity of information technology tools for greater efficiency and effectiveness in public administration. In the city of Louveira, the specific case analyzed the implementation of an information technology tool that is used throughout the prefecture, called the site as Citizen Card, which aims to document access and use of municipal public services, but the study a cut of the case was conducted to investigate the instrument as a management strategy to improve planning in the city, specifically in the health sector. The management of the Citizen Card system coupled to records in electronic health record gave greater reliability to the database of municipal health, enabling investigate and plot strategy defined for the management of the Unified Health System (SUS) site as well as allow better investigation the system deviations. Finally, we present questions about the SUS front system municipalization and still on and the issues of the health pact and its own Brazilian federal pact.